Normal modes for specific motions of macromolecules: application to the hinge-bending mode of lysozyme. - Brooks, B (1985)
A method is presented for finding particular normal modes for large molecules such as proteins and nucleic acids. The method is based on an iterative approach that extracts eigenvectors of interest from the full second-derivative matrix. Application of the method to the interdomain (hinge-bending) motion of lysozyme yields a frequency of 3.6 cm-1. This is similar to the value obtained from earlier adiabatic-energy-minimization studies. Analysis of the mode shows that the relaxation associated with the hinge bending is highly delocalized; that is, the dihedral angle and energy changes are distributed over many residues, including some (e.g., Trp-28) that are distant from the cleft and hinge region.